Penerapan Akad Musyarakah Mutanaqisah Pada Perumahan Syariah Aster Village Ciwastra Menggunakan Produk Pembiayaan Kredit Bank Syariah Indonesia - Utama, Sofyan Mei; Farid, Diana; Abdulah Pakarti, Muhammad Husni; Mabruri, Kemal Al Kautsar; Rohman, Hilma Fanniar (Jurnal Ilmiah Ekonomi Islam, 2023)
House sale and purchase transactions in the context of sharia have become a major concern in the development of Islamic economic models that are based on the principles of justice, equality, and compliance with Islamic law. One of the contracts proposed to fulfill these principles is the Musyarakah Mutanaqisah Agreement. This study aims to analyze the application of the Musyarakah Mutanaqisah Agreement on home ownership loans in aster village Islamic housing where the implementation of credit is carried out through a Bank mechanism in this case Bank Syariah Indonesia (BSI). The research method used is a qualitative approach with a case study approach. Data were obtained through interviews with related parties, analysis of transaction-related documents, and review of related literature. The results showed that the implementation of the Musyarakah Mutanaqisah contract in BSI Griya Hasanah financing has two contracts in it (hybrid contract). The first is that banks and customers cooperate (syirkah / musyarakah) to buy an asset, so the musyarakah contract in BSI Griya Hasanah financing is only limited to cooperation in the ownership of an asset. The second is ijarah. The asset that becomes the object of financing is leased (ijarah) to the customer with a rental payment which is assumed to be a profit that will be divided between the bank and the customer according to a predetermined ratio. The profit sharing obtained by the bank will be considered as profit for the bank. Meanwhile, the profit sharing received by the customer is diverted to buy the bank's hishah portion. Not only is there more than one contract, in this BSI Griya Hasanah financing scheme there are also two agreement contracts. The first agreement contract contains the Musyarakah Mutanaqisah contract itself, and the second agreement contract contains ijarah.